Job Satisfaction and Change Readiness: A Study of Global IME Bank - Balami, Surya (Interdisciplinary Journal of Innovation in Nepalese Academia, 2022)
Any organization’s innovation is the key factor for gaining sustained competitive advantage. In achieving the innovation, change is an important factor and to bring about the change, employees’ change readiness is indispensable. So, creating employees’ change readiness largely avoids the resistance to change. This study mainly attempts to explore the positions of employees’ job satisfaction and to analyze the impact of job satisfaction on change readiness. To explore the position, cross sectional research under descriptive research design and casual research design have been adopted respectively. Based on the primary data collected from branch managers of Global IME Bank, the researcher explored the impact of job satisfaction on change readiness. Under the descriptive statistics, minimum, maximum, mean and standard deviation have been used to describe the position of managers’ job satisfaction. Under the casual analysis, Karl Pearson’s correlation and regression analysis have been adopted to analyze the impact of job satisfaction on change readiness and test first hypothesis. Under the inferential statistics, independent sample t-test and analysis of variance have been adopted to test the second hypothesis. Cronbach’s Alpha has been calculated to test the reliability of data. The position of managers’ job satisfaction was found to be above to the average in investigated banks. It was also identified significant positive relationship between job satisfaction and change readiness and no significant difference in change readiness in different groups of gender, age, level of education and length of employment. This study proposes that managers should increase employees’ job satisfaction level to create employees’ change readiness so as to reduce the change resistance significantly and introduce the change successfully.